Identifikasi Drug Related Problems Pasien Hipertensi dengan Gagal Ginjal Kronik di Instalasi Rawat Inap RSUD Raja Ahmad Tabib Kepulauan Riau - Ruth Eva Betriana; Risma Sakti Pambudi; Khotimatul Khusna (STIKes Ibnu Sina Ajibarang, 2025)
Hypertension is one of the risk factors for cardiovascular disease and kidney disease with prevalence increasing every year. Medications for a long period of time and using a combination of drugs (polypharmacy) are at risk of Drug Related Problems (DRPs). DRPs are events or conditions associated with drug therapy that actually or potentially interfere with desired clinical health outcomes. The purpose of this study was to determine the identification of Drug Related Problems that occurred in hypertensive patients with chronic renal failure in the inpatient installation of Raja Ahmad Tabib Hospital Riau Islands. The research method used is non-experimental, descriptive and retrospective research. The number of samples was 60 who met the inclusion criteria. The sample used is data from medical records of hypertensive patients with chronic renal failure for the period January to December 2022. Based on the results of the study, it was found that 52 patients (86.67%) experienced DRPs, with the number of potential DRPs indications without therapy as many as 5 patients (8.33%), inappropriate drug selection as many as 2 patients (3.33%) and drug interactions. as many as 45 patients (75%).